2009
DOI: 10.1007/s00340-009-3697-3
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser written stress-induced Nd:Y3Al5O12 (Nd:YAG) channel waveguide laser

Abstract: Single tracks and pairs of tracks were written into undoped and Nd-doped YAG crystals using a commercial femtosecond laser system delivering pulses with pulse duration of 140 fs and pulse energies up to 10 mu J. The pulses were focused by a 50x microscope objective below the surface of the crystals. Due to the elasto-optical effect, stress-induced birefringence was observed in domains surrounding the single tracks and between the pairs of tracks. Waveguiding was demonstrated in certain channels in these domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
108
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(120 citation statements)
references
References 10 publications
9
108
2
1
Order By: Relevance
“…Refractive index profile of the waveguide recorded by QPm technique (http://www.iatia.com.au) under observation in the direction of femtosecond laser beam propagation is shown in Fig.3. The 1 kHz Ti:Sapphire laser always produces a negative PRICE in YAG single crystals (Okhrimchuk, 2005(Okhrimchuk, -a, 2005Siebenmorgen, 2009). It was reported that in the ceramic YAG doped with 2 at.% of Nd 3+ ions PRICE is negative too (Torchia, 2008).…”
Section: Waveguide Fabrication Technique and Architecturementioning
confidence: 98%
See 3 more Smart Citations
“…Refractive index profile of the waveguide recorded by QPm technique (http://www.iatia.com.au) under observation in the direction of femtosecond laser beam propagation is shown in Fig.3. The 1 kHz Ti:Sapphire laser always produces a negative PRICE in YAG single crystals (Okhrimchuk, 2005(Okhrimchuk, -a, 2005Siebenmorgen, 2009). It was reported that in the ceramic YAG doped with 2 at.% of Nd 3+ ions PRICE is negative too (Torchia, 2008).…”
Section: Waveguide Fabrication Technique and Architecturementioning
confidence: 98%
“…It was reported that in the ceramic YAG doped with 2 at.% of Nd 3+ ions PRICE is negative too (Torchia, 2008). However there is refractive index increase in the area closely adjacent to a track (Dubov, 2004;Siebenmorgen, 2009) that is due to elasto-optical effect. The waveguide is produced due to this phenomenon in these works.…”
Section: Waveguide Fabrication Technique and Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…Since the LYB:Eu is a potential laser crystal [10], these observations are of strong interest when considering possibilities to tune both structural and optical properties of this material by direct laser writing, especially for weaker crystal modifications related to waveguide writing for laser amplification applications [11][12][13][14][15]. Moreover, since such crystal is a low symmetry crystal, intensity thresholds for laser-induced modifications should significantly depend on the considered crystal orientation [16].…”
mentioning
confidence: 99%